“PARENTING CHALLENGES AND STRATEGIES IN NURTURING PRE-SCHOOL CHILDREN: A COMPREHENSIVE STUDY” (CAHIERS MAGELLANES-NS, 2024)
The challenges of parents and society is to rear children to realize their full potential in their foundation stage. The main challenge is how children grow, develop and how parents action influence children’s feelings and behaviour and their overall development. Good parenting is essential for care and development of pre-school children. Parenting is potentially a prominent process which affects preschooler’s physical, social, cognitive and academic development. Parenting in this period involves, balancing acceptance of child and his/her individuality with control. And giving reasons for rules in terms the child can understand, helping children master challenges, so they have successful experience in making things carrying out their plans. Parenting styles have a crucial role in children’s care and development (Holden & Edwards, 1989; Baumrind, 1991; Darling and Steinberg, 1993; Chao, 1994; Paulsen, 1994; Lorenz, Hoven, Andrews & Bird, 1995; Reiss, et al., 1995; Palmer & Holkin, 1996; Radzi & Zewska, Richardsorn, Dent, Flay, 1996, Holdren, 1997; Wuerido, Warner and Eyberg, 2002; Sabatini and Leiper, 2004; Dixon, Hareilton-Giachritis & Browne, 2005). Teachers and other childhood professionals are the key resource persons who disseminate information to the parents and encourage parents to choose the effective parenting style. Children’s behaviour and psychological development are linked to the style of parenting with which they have been raised. Parenting is ongoing interaction between parent, child and society. Parenting shape children’s character into mature adults who will learn and understand the nature of their own divinity and serving mankind with love. Effective parenting needs 3Fs (Firm, Fair and Friendly). Parents are very possessive and interfere in their children’s activities, so they are creating many problems and parenting challenges are more in the society. So, increase of support and security, feeding, bathing, toilet training, sleeping, fear and aggression, empathy, discipline, tragedy and school, playmates, attachment to parents increase parenting challenges. The objective of the study is to ascertain the parenting challenges towards preschool children and their development and wellbeing. A total of one hundred children (preschool age group) and one hundred parents were taken as the subject. Different scales were administered in the present study to asses the attitude of parents towards their preschool children. Data were derived from different districts and different schools of Odisha. Questionnaire method was adopted. For data analysis SPSS package was also adopted. The result of the present study revealed total parental attitude of preschool children. According to the findings of the study, preschool children had more feeding problems and less interested in food. Parents give maximum support and security when their children are sick and incase of problematic situation. They are also short tempered. This study suggests that preschoolers need constant supervision and interaction with their parents. They should spend sufficient quality time with their children.